Solve for z 12+6(z-2)=5z+3

Math
12+6(z-2)=5z+3
Simplify 12+6(z-2).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
12+6z+6⋅-2=5z+3
Multiply 6 by -2.
12+6z-12=5z+3
12+6z-12=5z+3
Combine the opposite terms in 12+6z-12.
Tap for more steps…
Subtract 12 from 12.
6z+0=5z+3
Add 6z and 0.
6z=5z+3
6z=5z+3
6z=5z+3
Move all terms containing z to the left side of the equation.
Tap for more steps…
Subtract 5z from both sides of the equation.
6z-5z=3
Subtract 5z from 6z.
z=3
z=3
Solve for z 12+6(z-2)=5z+3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top